Analgesic effect of clobazam in chronic low‐back pain but not in experimentally induced pain. (18th April 2017) - Schliessbach, J.; Vuilleumier, P.H.; Siegenthaler, A.; Bütikofer, L.; Limacher, A.; Juni, P.; Zeilhofer, H.U.; Arendt‐Nielsen, L.; Curatolo, M.
Abstract: Background: Chronic pain is frequently associated with hypersensitivity of the nervous system, and drugs that increase central inhibition are therefore a potentially effective treatment. Benzodiazepines are potent modulators of GABAergic neurotransmission and are known to exert antihyperalgesic effects in rodents, but translation into patients are lacking. This study investigates the effect of the benzodiazepine clobazam in chronic low‐back pain in humans. The aim of this study is to explore the effect of GABA modulation on chronic low‐back pain and on quantitative sensory tests. Methods: In this double‐blind cross‐over study, 49 patients with chronic low‐back pain received a single oral dose of clobazam 20 mg or active placebo tolterodine 1 mg. Pain intensity on the 0–10 numeric rating scale and quantitative sensory tests were assessed during 2 h after drug intake. Results: Pain intensity in the supine position was significantly reduced by clobazam compared to active placebo (60 min: 2.9 vs. 3.5, p = 0.008; 90 min: 2.7 vs. 3.3, p = 0.024; 120 min: 2.4 vs. 3.1, p = 0.005). Pain intensity in the sitting position was not significantly different between groups. No effects on quantitative sensory tests were observed. Conclusions: This study suggests that clobazam has an analgesic effect in patients with chronic low‐back pain. Muscle relaxation or sedation may have contributed to the effect. Development of substances devoid of these side effects would offer the potential to further investigate the antihyperalgesic action of GABAergic compounds. Significance: Modulation of GABAergic pain‐inhibitory pathways may be a potential future therapeutic target.